2018
DOI: 10.1093/ct/qtx005
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Communication Design Logics: A Theory of Communicative Intervention and Collective Communication Design

Abstract: Theorizing communication as design can support the development of theories of intervention by focusing attention not just on how groups, organizations, and communities communicate, but also on how they make and try to enact choices about their communication. We posit a theory of organizational communication design logics aimed at clarifying how collectives intervene in their own communication. We argue that collective communication design (CCD) is comprised of (a) individuals' overlapping communication designs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 43 publications
0
15
0
1
Order By: Relevance
“…Organizational communication is described as the process by which the members share information related to jobs or exchange emotion among the members in the organization (Chen et al, 2005;Choi et al, 2018). In the past, organizational communication was viewed as providing information to the public (one-way communication), whereas more recently organizational communication aims for balanced effects for both parties through social interaction, persuasion and mutual understanding (two-way communication) (Barbour et al, 2018;Cornelissen, 2004). Also, organizational communication allows members to increase their understanding of members' tasks and roles and the rules, policies and practices of organizations.…”
Section: Effect Of Transformational Leadership and Organizational Justice On Knowledge Sharingmentioning
confidence: 99%
“…Organizational communication is described as the process by which the members share information related to jobs or exchange emotion among the members in the organization (Chen et al, 2005;Choi et al, 2018). In the past, organizational communication was viewed as providing information to the public (one-way communication), whereas more recently organizational communication aims for balanced effects for both parties through social interaction, persuasion and mutual understanding (two-way communication) (Barbour et al, 2018;Cornelissen, 2004). Also, organizational communication allows members to increase their understanding of members' tasks and roles and the rules, policies and practices of organizations.…”
Section: Effect Of Transformational Leadership and Organizational Justice On Knowledge Sharingmentioning
confidence: 99%
“…Because of the integrated nature of digital communication environments and their versatile possibilities, it can be challenging for employees to perceive these environments as a single, coherent platform instead of as several different communication tools or to understand the logic underlying how the various parts of the platform should be used (Barbour, Gill & Barge 2018;Treem et al 2019). Thus, it is important to collectively discuss how these environments should be used, identify the leaders' and employees' expectations regarding the use of digital communication environments, and determine how employees can best utilize them.…”
Section: Purposesmentioning
confidence: 99%
“…Moreover, more study are found such as to link Organizational Resources and Work Engagement (Salanova et al, 2005); CEO Norms (Griffin, 2015); Collective action (Barnhardt, 2016); COE to link with Firm performance (Barrick et al, 2015); Model of COE (Flanagin et al, 2006); Constructive Leadership (Wei et al, 2016); Collective Engagement Identity (Fachrunnisa and Tjahjono, 2018); impact of Delegation on COE (Özdemir and Temel, 2017); organizational stressors on collective organizational (Molines et al, 2017); The role of civic engagement Jason (Carbone and McMillin, 2019); Neighborhood collective efficacy Jason (Carbone and McMillin, 2019); Organizational Communication Design (Joshua B. Barbour et al, 2018); Cognitive Collective Engagement (Fachrunnisa and Tjahjono, 2018); Collective psychological capital (Wu and Chen, 2018); Collective Engagement Creates Competitive Advantage (Eldor, 2019); Health-Related HRM (Huettermann and Bruch, 2019); Collective engagement (Wilson, 2019); Employee and collective voice engagement (Gruman and Saks, 2020); Tool to Develop Collective Organizational (Retolaza et al, 2020); the role of CEO on Entrepreneurial…”
Section: Introductionmentioning
confidence: 99%